2018
DOI: 10.1038/s41467-018-05202-8
|View full text |Cite
|
Sign up to set email alerts
|

MAIT cells protect against pulmonary Legionella longbeachae infection

Abstract: Mucosal associated invariant T (MAIT) cells recognise conserved microbial metabolites from riboflavin synthesis. Striking evolutionary conservation and pulmonary abundance implicate them in antibacterial host defence, yet their functions in protection against clinically important pathogens are unknown. Here we show that mouse Legionella longbeachae infection induces MR1-dependent MAIT cell activation and rapid pulmonary accumulation of MAIT cells associated with immune protection detectable in immunocompetent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
309
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 190 publications
(330 citation statements)
references
References 56 publications
16
309
3
2
Order By: Relevance
“…The bacterial load was significantly lower in wild‐type mice that had been previously exposed to 5‐OP‐RU. This is the first encouraging example of actually examining 5‐OP‐RU to serve as a vaccine .…”
Section: Mait Cells In Vaccines Against Microbial Infectionmentioning
confidence: 89%
“…The bacterial load was significantly lower in wild‐type mice that had been previously exposed to 5‐OP‐RU. This is the first encouraging example of actually examining 5‐OP‐RU to serve as a vaccine .…”
Section: Mait Cells In Vaccines Against Microbial Infectionmentioning
confidence: 89%
“…These are now produced by the NIH Tetramer Core Facility and are permitted to be distributed by the University of Melbourne. The tetramer technology in combination with recently established infection models (Rahimpour et al., ; Wang et al., ) makes it possible to expand and characterize MAIT cells with precision. This unit describes practical step‐by‐step protocols and should provide a technical platform for the MAIT cell research community.…”
Section: Commentarymentioning
confidence: 99%
“…If the recipients (Support Protocol 5) are RAG2 − / − γC − / − mice, any transferred T cells, including MAIT cells, will spontaneously expand (known as homeostatic proliferation). We have observed that a few contaminating non‐MAIT T cells (<1%) could account for up to 10% to 15% of all transferred T cells after 2 weeks, suggesting different rates of proliferation (Wang et al., ). This will impact the recipients’ immune capacity and may produce unexpected results.…”
Section: Commentarymentioning
confidence: 99%
See 2 more Smart Citations